2005
DOI: 10.1074/jbc.m504953200
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of Genetically Modified Synechocystis sp. PCC 6803 Photosystem II Core Complexes Containing Carotenoids with Shorter π-Conjugation than β-Carotene

Abstract: ␤-Carotene has been identified as an intermediate in a secondary electron transfer pathway that oxidizes Chl Z and cytochrome b 559 in Photosystem II (PS II) when normal tyrosine oxidation is blocked. To test the redox function of carotenoids in this pathway, we replaced the -carotene desaturase gene (zds) or both the zds and phytoene desaturase (pds) genes of Synechocystis sp. PCC 6803 with the phytoene desaturase gene (crtI) of Rhodobacter capsulatus, producing carotenoids with shorter conjugated -electron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…However, this level of enzymatic complexity is reminiscent of the complexity seen in converting phytoene to lycopene. Although a single enzyme, CrtI, can perform the same suite of reactions (22,25,34,46,50), two desaturases and at least one isomerase are required to convert phytoene into lycopene in GSB and most cyanobacteria (1,3,4,6,7,19,21,34,40,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this level of enzymatic complexity is reminiscent of the complexity seen in converting phytoene to lycopene. Although a single enzyme, CrtI, can perform the same suite of reactions (22,25,34,46,50), two desaturases and at least one isomerase are required to convert phytoene into lycopene in GSB and most cyanobacteria (1,3,4,6,7,19,21,34,40,43).…”
Section: Discussionmentioning
confidence: 99%
“…These functions are very important in photosynthetic bacteria, and complete inactivation of the carotenogenic pathway in the cyanobacterium Synechocystis sp. strain PCC 6803 has been possible only in strains adapted to photoheterotrophic growth on glucose (3,4).…”
mentioning
confidence: 99%
“…species were identified (Car A at 982 nm and Car B at 1,027 nm). We note that for PS II containing carotenoids with less than 11 conjugated double bonds (Bautista et al 2005), there is no increase in absorption in the 1,030-1,100 nm region during extended illumination, which suggests that the absorption changes in this region observed here and in ferricyanide-treated PS II are due to the properties of PS II, and not due to the changes in the background absorption from water that could be produced by a heating artifact.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, genetic manipulation of the carotenoid synthesis suggested that PSII assembly requires the presence of a carotenoid with at least one β-ionylidene ring, which may play a structural role in early stages of assembly (Bautista et al 2005b). …”
Section: Earlier Studies On Carotenoid Mutants In Cyanobacteriamentioning
confidence: 99%
“…Previously it has been suggested that β-carotene is vital for synthesis of D1 protein in the green alga, Chlamydomonas reinhardtii (Trebst and Depka 1997) as well as in the cyanobacterium, Synechocystis (Masamoto et al 2004). Moreover, genetic manipulation of the carotenoid synthesis suggested that PSII assembly requires the presence of a carotenoid with at least one β-ionylidene ring, which may play a structural role in early stages of assembly (Bautista et al 2005b). On the other hand, it is interesting to note that carotenoidless mutants of purple bacteria with type-2 RCs have normal photosynthesis.…”
Section: Structural and Functional Consequences Of The Carotenoid Defmentioning
confidence: 99%